Objectives and Design of the Russian Acute Coronary Syndrome Registry (RusACSR). Issue 1 (22nd December 2015) - Gridnev, Vladimir I.; Kiselev, Anton R.; Posnenkova, Olga M.; Popova, Yulia V.; Dmitriev, Viktor A.; Prokhorov, Mikhail D.; Dovgalevsky, Pavel Ya.; Oschepkova, Elena V.; ,
ABSTRACT: The Russian Acute Coronary Syndrome Registry (RusACSR) is a retrospective, continuous, nationwide, Web‐based registry of patients with acute coronary syndromes (ACS). The RusACSR is a database that uses a secure Web‐based interface for data entry by individual users. Participation in the RusACSR is voluntary. Any clinical center that provides health care to ACS patients can take part in the RusACSR. The RusACSR enrolls ACS patients who have undergone care in Russian hospitals from February 2008 to the present. Key data elements and methods of data analysis in the RusACSR are presented in this article. Up to 2015, 213 clinical centers from 36 regions of Russia had participated in the RusACSR. Currently, the database contains data on more than 250 000 ACS patients who underwent care from 2008 to 2015. Some current problems are highlighted in this article. The RusACSR is a perspective project for different epidemiologic studies in Russian ACS patients.